2013
DOI: 10.5380/rf.v44i1.31356
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF WHEELED TYPES OF A Skidder ON PRODUCTIVITY AND COST OF THE FOREST HARVESTING

Abstract: The objective of this study was to evaluate the influence of different wheel types of a skidder on productivity and cost of Pinus taeda L. wood extraction. The study was conducted in a forestry company located in the municipality of Mandirituba, Paraná state, Brazil. The technical and cost analyses included a time and motion study of the wood extraction activity. The productivity, operative efficiency, energy consumption and the production and operational costs were determined for the machines with different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
1
9
0
4
Order By: Relevance
“…The large amount of time taken by the empty and loaded travel stages is in agreement with several authors, who affirm that this type of machine is active throughout most of the operational cycle, that is, undertaking empty and loaded travel (BEHJOU et al, 2008;LOPES et al, 2014). This shows that, in order to optimize the extraction operation with the skidder, it is necessary to perform the operation over shorter distances, because over longer distances, the time consumed during travel increases.…”
Section: Discussionsupporting
confidence: 88%
“…The large amount of time taken by the empty and loaded travel stages is in agreement with several authors, who affirm that this type of machine is active throughout most of the operational cycle, that is, undertaking empty and loaded travel (BEHJOU et al, 2008;LOPES et al, 2014). This shows that, in order to optimize the extraction operation with the skidder, it is necessary to perform the operation over shorter distances, because over longer distances, the time consumed during travel increases.…”
Section: Discussionsupporting
confidence: 88%
“…This result, although it does not show a significant difference, should be considered relevant, since, with the introduction of a maintenance system based on preventive maintenance, the maintenance cost of the machines was reduced. The values obtained for the maintenance cost of skidder were above the costs observed by Lopes et al (2014), studying the forest tractor skidder in the extraction of wood, in which they observed an average maintenance cost of R$ 102.30 per hour worked.…”
Section: Discussionmentioning
confidence: 50%
“…In this sense, researchers infer that forest harvesting activities represent high costs in the forest productive process, and can reach 50% or more of the industry wood costs, having, possibly, a great economic impact on the forest-based industry (GUEDES et al, 2017). Lopes et al (2014) and Silva et al (2010), studying the extraction and logging operations, respectively, identified that only the cost of mechanical maintenance can represent up to 60% of forest harvesting machine total cost, being clear the importance of the maintenance sector within the activity of wood harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Dado o cenário atual, as empresas vêm buscando avaliar todo futuro investimento e, nesse contexto, a manutenção de equipamentos de colheita florestal mostra-se como ponto chave, uma vez que seus custos podem variar de 50 a 60% do custo total do equipamento (SILVA et al, 2010;LOPES et al, 2014). Yamashina (2000) comenta que um dos principais modelos de manutenção utilizados é o World Class Maintenance (WCM), que utiliza como base a manutenção preventiva.…”
Section: Introductionunclassified